Comparative study on the supercapacitive properties of PANI nanofibers, nanotubes, and nanospheres. (June 2020) - Xiong, Shanxin; Zhang, Yong; Wang, Yuyun; Wu, Bohua; Chu, Jia; Wang, Xiaoqin; Zhang, Runlan; Gong, Ming; Li, Zhen; Chen, Zhenming
In this study, polyaniline (PANI) nanostructures with different morphologies (nanofibers, nanotubes, and nanospheres) were obtained via interfacial polymerization, rapid mixing reaction, and hydrothermal method. The influences of the synthesis methods on the morphologies and supercapacitive properties of PANI nanostructures were investigated. The chemical structures of materials were characterized by Fourier-transform infrared and Raman spectroscopies. Scanning electron microscopy and transmission electron microscopy images were used to explore the morphologies of PANI nanostructures. N2 adsorption–desorption isotherm, cyclic voltammetry, charge–discharge test, and electrochemical impedance spectroscopy were used to characterize the pore distribution, electrochemical, and supercapacitive properties of PANI nanostructures. The results show that PANI nanotubes (PANI-T) exhibit the best electrochemical performances among three kinds of PANI nanostructures. The PANI-T exhibits high specific capacitances of 648 and 290 F g −1 at current densities of 0.5 and 10 A g −1, respectively, indicating its good supercapacitive property and rate capability. The enhanced electrochemical and supercapacitive performances can be attributed to its hollow nanotube structure.